Mindfulness from a Christian Perspective - Sitanggang, Murni Hermawaty (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2024)
Abstract: Mindfulness has long been popular among psychologists and medical workers as the best answer to help people focus so they can avoid or prevent stress. Some Christians also practice mindfulness and make it part of their worship rituals. However, because it is considered identical to Buddhism and East religions, some believers refuse to practice this for fear of syncretism. Thus, this article explores to what extent believers could accept and practice mindfulness. This study used a qualitative method with a library approach. The writer collects data from various literature related to discussing and analyzing the topic. From the study, the writer concludes that although worldly mindfulness offers more positive aspects than negative ones, believers should avoid it and practice biblical mindfulness instead. The true Christian mindfulness centers on God and involves His words.Â Keywords: mindfulness, meditation, stress, happiness